(untitled) - Drake, Ellen (Philadelphia.PA, 2007)
Written by transcriptionists for transcriptionists, this quick, easy-to-use reference provides correct spelling and capitalization of drugs, gives their designated use, and usual methods of administration. In addition, it offers cross-references between brand names and generic drugs and includes other "consumable" products, such as in vitro testing kits, radiographic contrast and imaging agents, and wound dressings. Overall, this book features 200 drug classes in the main list with a brief description of the therapeutic use and/or method of action common to drugs in the class.
Keywords: Drugs,Pharmaceutical Preparations,Thuốc,Chế phẩm dược